The Scientific Research On The Issue Of Bilingualism Conducted By Cis Scholars (Texas Journal of Multidisciplinary Studies, 2024)
This article discusses the emergence of bilingualism, highlighting the necessity of language contact between different nations, the impact of languages' mutual interaction, and the in-depth, comprehensive, and advanced research conducted by CIS scholars on these phenomena.